2014
DOI: 10.1080/15476286.2014.996462
|View full text |Cite
|
Sign up to set email alerts
|

The role of MicroRNAs in Osteoclasts and Osteoporosis

Abstract: These authors contributed equally to this work. Keywords: MicroRNA, osteoclast, osteoporosisAbbreviations: GM-CSF, Granulocyte macrophage colony-stimulating factor; MiRNA, microRNA; 3'-UTR; 3' untranslated region; BMMs, bone marrow macrophages; PDCD4, programmed cell death 4; FasL, Fas ligand; PIO, particle-induced osteolysis; Calcr, calcitonin receptor; RDX, radixin; M-RIP, myosin phosphatase-Rho interacting protein; ITGA5, integrin a5; Fzd3, frizzled 3; ALP, alkaline phosphatase; TRAP, tartrate-resistant aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 81 publications
2
108
0
Order By: Relevance
“…(64) Other miRNAs, such as miR-21 and miR-378, have been implicated in osteoclastogenesis. (65) In particular, miR-21 is of interest because miR-21 is not only known as "inflamma-miR," (66) but has been shown to mediate RANKL-induced osteoclast differentiation (67) and inhibit osteoclast apoptosis. (68) Given that we found significantly higher serum miR-21 serum levels in DMFx than in DM subjects and that DMFx were described to have more cortical porosity, (29) osteoclast dysfunction/or prolonged osteoclast survival might be a potential mechanisms that could explain the higher fracture risk in the DMFx patients.…”
Section: Discussionmentioning
confidence: 99%
“…(64) Other miRNAs, such as miR-21 and miR-378, have been implicated in osteoclastogenesis. (65) In particular, miR-21 is of interest because miR-21 is not only known as "inflamma-miR," (66) but has been shown to mediate RANKL-induced osteoclast differentiation (67) and inhibit osteoclast apoptosis. (68) Given that we found significantly higher serum miR-21 serum levels in DMFx than in DM subjects and that DMFx were described to have more cortical porosity, (29) osteoclast dysfunction/or prolonged osteoclast survival might be a potential mechanisms that could explain the higher fracture risk in the DMFx patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study confirmed that Dex acts on osteoblasts to up-regulate the expression of RANKL, which indirectly affects osteoclast differentiation and bone resorption (Shi et al, 2014). Furthermore, accumulating evidence demonstrates that miRNAs are involved in RANKL-induced osteoporosis (Tang et al, 2014). In the current study, we demonstrated that the inhibitory effect of miR-338-3p on osteoclast differentiation and bone resorption could be reversed by exogenous RANKL treatment, suggesting that miR-338-3p inhibited GC-induced osteoporosis by targeting RANKL expression.…”
Section: Discussionmentioning
confidence: 93%
“…miRNAs have been implicated in various pathophysiological events including embryogenesis, organogenesis, differentiation, metabolism, proliferation, and apoptosis (Couzin, 2007). Recent research on osteoclasts has focused on miRNAs as they have been shown to play crucial roles in their differentiation and function, indicating that miRNAs are novel regulatory factors of osteoclastogenesis (Tang et al, 2014). Therefore, miRNAs may represent new therapeutic targets for the pharmacological control of bone diseases.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs such as miR-223, miR-103a, and miR-140 have been reported to regulate bone metabolism by modulating bone formation, reabsorption, and osteoblast-osteoclast activity (140,141). miRNA expression profiling data in osteoporosis and osteoporotic fracture patients have clearly described that miRNAs play a crucial role in bone metabolism.…”
Section: Microrna: Regulator Of Bone Remodeling and Biomarker In Ostementioning
confidence: 99%